Task Aligned Technology: Enhancing Cross Unit Collaboration in Remote Work Environments - Maulidiyah, Ummi Masrufah; Silvanie, Astried; Sugianto (Indonesian Scientific Publication, 2025)
The growing prevalence of remote and hybrid work models has transformed how organizations coordinate tasks and collaborate across functional units. This study investigates whether IT media fit moderates the relationship between remote work intensity and cross unit collaboration. Drawing on Media Synchronicity Theory (MST), the research posits that communication media must align with task requirements particularly synchronicity needs to enhance collaboration outcomes. A quasi experimental, longitudinal design was used, analyzing weekly team level data from digital trace logs (Slack, Microsoft Teams) and surveys assessing remote work intensity and IT media alignment. The study employed Generalized Linear Mixed Models (GLMM) with interaction terms to evaluate the moderating effect of IT media fit. Key findings indicate that remote work alone does not significantly improve collaboration metrics such as network centrality or cross functional reply rates. However, in conditions of high IT media fit, remote work intensity positively correlates with more robust cross unit collaboration. These results were robust across multiple model specifications and validated through lagged temporal analysis, bias checks, and alternative statistical techniques. This research extends MST by incorporating the emotional and contextual dimensions of digital communication tools and emphasizing the need for tool task synchronicity in remote settings. The study provides actionable recommendations for organizations, including aligning communication tools with specific task types, training teams in digital collaboration practices, and designing adaptive communication policies. As digital collaboration becomes central to modern organizational life, the strategic fit between media and task emerges as a vital determinant of remote work effectiveness.